PENGARUH ALOKASI DANA DESA, JUMLAH PENDUDUK DAN LUAS LAHAN TERHADAP REALISASI PENERIMAAN PBB-P2 KABUPATEN SIGI - Wawan, Ade (Katalogis, 2017)
The Aims of this research are ; 1) to determine the impact of village funds allocation, total population and lands on the realization of property tax both in urban adn rural area (PBB-P2); 2) to determine the impact of village funds allocation on the realiation of property tax both in rural and urban areas (PBB-P2); 3) to determine the impact of total population on the realiation of property tax both in rural and urban areas (PBB-P2); 4) to determine the impact of lands on the realiation of property tax both in rural and urban areas (PBB-P2). The research involves 64 villages from 15 districts i Sigi Regency that selected through purposive sampling. Method of research is descriptive quantitative and qualitative with multiple linear regression analysis. The results have found that: 1) Village fund allocation, total population and lands simultaneously have positive and significant impact on the realization of property tax both in urban adn rural area (PBB-P2) with adjusted R-Square of 0,561 or 56,10% on significance 0,000; 2) Village Funds allocation partially has insignificant impact on the realization of property tax both in urban adn rural area (PBB-P2) with tvalue of 0,759 on significance of 0,431; 3) total popultion partially has significant impact on the realization of property tax both in urban adn rural area (PBB-P2) with tvalue Âof 3,861 0n significance of 0,001; 4) Lands partially has significant impact on the realization of property tax both in urban adn rural area (PBB-P2) with tvalue of 3,466 on significance of 0,000.